1977
DOI: 10.1149/1.2133520
|View full text |Cite
|
Sign up to set email alerts
|

On the Composition of the Passivating Films Formed on Aluminum in Chromate Solutions

Abstract: The chemical constitution of the passive oxide films formed on aluminum in chromate and chromate/chloride solutions under simple immersion (at open-circuit potential) and under anodic polarization has been investigated by means of x-ray photoelectron spectroscopy. It has been shown that these films, whose thickness is comparable with the mean escape depth of photoelectrons, are composed of a mixture of hydrated chromium (lII) oxide, aluminum (III) oxide, and chromium (VI) specms. A considerable amount of chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

1977
1977
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 5 publications
0
21
0
1
Order By: Relevance
“…For example, using XPS, Treverton and Davies have observed levels between 0%3 and 15%.2 Much higher levels of Cr6`have also been reported. Koudelkova et al detected D20% Cr6`, 6 Hagans and Haas D 60%,7 Davenport and Isaacs detected D50% Cr6`using XANES33 and Lytle et al8 detected only 23% Cr6à lso using XANES. The XANES studies by Hawkins et al10 on oxide Ðlms of di †erent thicknesses which had been immersed in chromate/chloride solution demonstrated qualitatively that the amount of Cr6`incorporated into the protective coating depended on the Ñaw density, i.e.…”
Section: As-prepared Coatingmentioning
confidence: 98%
“…For example, using XPS, Treverton and Davies have observed levels between 0%3 and 15%.2 Much higher levels of Cr6`have also been reported. Koudelkova et al detected D20% Cr6`, 6 Hagans and Haas D 60%,7 Davenport and Isaacs detected D50% Cr6`using XANES33 and Lytle et al8 detected only 23% Cr6à lso using XANES. The XANES studies by Hawkins et al10 on oxide Ðlms of di †erent thicknesses which had been immersed in chromate/chloride solution demonstrated qualitatively that the amount of Cr6`incorporated into the protective coating depended on the Ñaw density, i.e.…”
Section: As-prepared Coatingmentioning
confidence: 98%
“…The susceptibility of aluminium alloys to localized corrosion strongly depends on the distribution and electrochemical properties of intermetallic compounds (IMCs) and second phase particles [3][4][5][6][7][8][9]. Aluminium alloys for aerospace applications are protected from the aggressive environment using multi-layered coating systems based on the chemistry of chromates [10][11][12][13][14][15][16][17]. A suitable candidate for chromate replacement has not yet been developed for the most demanding applications [10].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the susceptibility to localized corrosion, aluminum alloys for aerospace applications are protected from the aggressive environment using multi-layered coating systems based on the chemistry of chromates [18][19][20][21][22][23][24][25]. It has been shown that the formation of a Cr 3+ monolayer inhibits oxygen and further Cr 6+ reduction [18,[27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%